Catastrophic health expenditure: a community-based study in Sarawak, Malaysia - Johnny, Pangkas; Md Mizanur, Rahman; Raili, Suhaili (Medip Academy, 2021)
Background: Accessing health services can lead to individuals having to pay catastrophic proportions of their available income and push many households into poverty. The aim of the study was to estimate the catastrophic health expenditure in respect of household expenditure and to determine the factors affecting it in Sarawak, Malaysia. Methods: We collected household expenses based on a recall period of one month through a face-to-face interview. We calculated the catastrophic health expenditure in terms of 10% of household expenditure and 40% of the capacity to pay. A binary logistic regression analysis was done to determine the factors associated with catastrophic health expenditure. Data analysis was done by IBM SPSS version 27.0. Results: The analysis revealed that one-quarter (25.7%) of the household expenditure was on food, equivalent to MYR 373.562, and 18.83% of the total household expenditure was on health (MYR 292.83). About two-fifths (37.4%) of the households had incurred catastrophic health expenditure on 10% of household consumption and 15.6% catastrophic health expenditure on 40% of household expenditure. Multivariate analysis with forward and backward linear regression methods revealed that age, gender, family size, socioeconomic status, and chronic illness appeared to be potential predictors of 10% catastrophic health expenditure (p<0.05). In contrast, socioeconomic status and level of education appeared to be potential predictors for 40% catastrophic health expenditure (p<0.05). Conclusions: Subsidised health care may not protect against the occurrence of catastrophic health expenditure among the household in the lower socioeconomic status. Family size and age also could affect household catastrophic health expenditure.